ASUHAN KEPERAWATAN KLIEN GANGGUAN SISTEM IMUNOLOGI (HIV/AIDS) DENGAN KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS - Kurniawati, Kurniawati (Jurnal EDUNursing, 2018)
AIDS defined by the Center for Disease Control and Prevention as HIV infection with indicator of accompanist disease such as (1) opportunistic infections; (2) cancer; (3) the shrinking syndrome; (4) neurologic disease; and (5) recurrent pneumonia; or HIV infection and CD4 <200 (Valentine, 2007). AIDS is the biggest community health problem in the world. Almost in every country this disease was alive and including in Indonesia (Irianto, 2014). Human immunodeficiency virus was selectively infected and destroys the cell which contain CD4-lymphocyte T4 (helper / inducer) and macrophage / monocyte cell system. The impact of HIV/AIDS was complicated and the nurses are important to help and solve this problem among HIV/AIDS patients. The aims of this paper was to know the nursing care of HIV / AIDS patients with ineffective of airway breathing at Cempaka Pavilion of RSUD Jombang. In this paper, the researcher was gave nursing care to HIV/AIDS patient who had ineffective of airway breathing. The methodology of this study used the nursing process stages of the case with ineffective airway breathing. After giving the nursing care among HIV / AIDS patients, the conclusions of this study are ineffective of airway breathing, inadequate of nutrition, damage of oral mucous membrane, ineffectiveness coping, and intolerance of activities. The success of the treatment depends on the cooperation between patient, family and nurse.Keywords: Immunological System, airway